Association of plasma miR-223 and platelet reactivity in patients with coronary artery disease on dual antiplatelet therapy: A preliminary report. (September 2015) - Chyrchel, Bernadeta; Totoń-Żurańska, Justyna; Kruszelnicka, Olga; Chyrchel, Michał; Mielecki, Waldemar; Kołton-Wróż, Maria; Wołkow, Paweł; Surdacki, Andrzej
Abstract Decreased plasma levels of microRNA-223 (miR-223), predominantly of platelet origin, were proposed as a surrogate marker of efficacy of antiplatelet therapy. However, higher on-treatment platelet reactivity was associated with lower plasma miR-223 in patients with coronary artery disease (CAD) on dual antiplatelet therapy (DAPT) including clopidogrel and aspirin. Our aim was to compare plasma miR-223 and platelet reactivity in CAD patients on DAPT with newer P2Y12 antagonists vs. clopidogrel. We studied 21 men with CAD admitted to our centre owing to a non-ST-elevation acute coronary syndrome, and with an uncomplicated hospital course. From the day of admission, the patients were receiving either clopidogrel (n = 11) or prasugrel/ticagrelor (n = 10) in addition to aspirin. Before discharge, miR-223 expression in plasma was estimated by quantitative polymerase chain reaction using the comparative Ct method relative to miR-16 as an endogenous control. Multiple electrode aggregometry was used to assess platelet aggregation in response to adenosine diphosphate (ADP). ADP-induced platelet reactivity was decreased in the patients treated with prasugrel or ticagrelor compared with those on clopidogrel (mean ± SD: 139 ± 71 vs. 313 ± 162 arbitrary units [AU]*min, p = 0.006), due to a more potent antiplatelet activity of the novel P2Y12 antagonists. Consequently, six out of seven patients in the lower tertile of the ADP-induced platelet aggregation were treated with the newer P2Y12 blockers, whereas six out of seven patients in the upper tertile were on clopidogrel. Plasma miR-223 was elevated with decreasing platelet reactivity (Spearman's rho = –0.52; p = 0.015 for trend), being significantly higher in the lower tertile of the ADP-induced platelet aggregation (median [range]: 1.06 [0.25–2.31]) vs. the upper tertile (0.20 [0.13–2.30]) (p = 0.04). In conclusion, our preliminary results argue against the notion of low plasma miR-223 as a marker of platelet responsiveness to DAPT. On the contrary, more potent platelet inhibition associated mainly with newer P2Y12 antagonists appears to coincide with higher miR-223 relative to the subjects with attenuated responsiveness to DAPT.